2021
DOI: 10.3389/fonc.2021.671892
|View full text |Cite
|
Sign up to set email alerts
|

A Liquid-Liquid Phase Separation-Related Gene Signature as Prognostic Biomarker for Epithelial Ovarian Cancer

Abstract: ObjectiveThe aim of the present study was to construct and test a liquid-liquid phase separation (LLPS)-related gene signature as a prognostic tool for epithelial ovarian cancer (EOC).Materials and MethodsThe data set GSE26712 was used to screen the differentially expressed LLPS-related genes. Functional enrichment analysis was performed to reveal the potential biological functions. GSE17260 and GSE32062 were combined as the discovery to construct an LLPS-related gene signature through a three-step analysis (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Currently, several bioinformatics signatures have been constructed in other tumors (27,28). Qiu et al constructed the signature of 11 LLPS-related genes in ovarian cancer by bioinformatics analysis, and accurately stratified the prognosis of ovarian cancer patients, among which patients in the high-risk group had significantly worse prognosis (29). And they found that LLPS-related genes were involved in several cancer-related pathways, such as MAPK signaling, cell cycle and DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several bioinformatics signatures have been constructed in other tumors (27,28). Qiu et al constructed the signature of 11 LLPS-related genes in ovarian cancer by bioinformatics analysis, and accurately stratified the prognosis of ovarian cancer patients, among which patients in the high-risk group had significantly worse prognosis (29). And they found that LLPS-related genes were involved in several cancer-related pathways, such as MAPK signaling, cell cycle and DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Genetics frontiersin.org assess the effects of LLPS in the prediction of tumor prognosis in ovarian epithelial cancer and lung cancer (Qiu et al, 2021;Zhuge et al, 2021). These two studies showed that LCGs were useful in distinguishing subgroups in which one group had a better prognosis, while the other had a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The potential prognostic value of LLPS-related molecular has also received increasing attention. Qiu et al constructed a LLPS-related GS as a prognostic tool for epithelial ovarian cancer [ 17 ]. Our analysis might firstly develop the novel LLPS-related GS for predicting the prognosis of LGG.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the aberration of liquid-liquid phase separation involves in many human diseases, including neurodegenerative diseases [ 14 ] and cancer [ 15 ]. Previous studies suggested that LLPS-related gene signature can be used as a prognostic marker for hepatocellular carcinoma [ 16 ] and ovarian cancer [ 17 ]. Thus, we hypothesized that LLPS-related genes may be potential prognostic markers that could contribute to the further classification of LGG.…”
Section: Introductionmentioning
confidence: 99%